2019
DOI: 10.1093/jac/dkz315
|View full text |Cite
|
Sign up to set email alerts
|

Towards endemicity: large-scale expansion of the NDM-1-producing Klebsiella pneumoniae ST11 lineage in Poland, 2015–16

Abstract: Objectives In 2015 and 2016 Poland recorded rapid proliferation of New Delhi MBL (NDM)-producing Enterobacterales, with at least 470 and 1780 cases, respectively. We addressed the roles of the Klebsiella pneumoniae ST11 NDM-1 outbreak genotype, already spreading in 2012–14, and of newly imported organisms in this increase. Methods The study included 2136 NDM-positive isolates identified between April 2015 and December 2016, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…NDM-CRE, highlighting the risk of rapid emergence and disseminations of uncommon variants of CPE within healthcare facility networks, as recently reported in other European countries [6,7]. Tuscany has a comprehensive and effective microbiological surveillance system, yet the increase in NDM-CRE cases was detected with some delay.…”
Section: Public Health Implications and Conclusionmentioning
confidence: 74%
See 1 more Smart Citation
“…NDM-CRE, highlighting the risk of rapid emergence and disseminations of uncommon variants of CPE within healthcare facility networks, as recently reported in other European countries [6,7]. Tuscany has a comprehensive and effective microbiological surveillance system, yet the increase in NDM-CRE cases was detected with some delay.…”
Section: Public Health Implications and Conclusionmentioning
confidence: 74%
“…NDM-CRE are able to hydrolyse almost all beta-lactams and are not inhibited by currently available beta-lactamase inhibitors, including the new ones avibactam and vaborbactam [4]. NDM-CRE were first described in 2008 in Sweden and subsequently reported across Europe [1,5], resulting in growing concern for these pathogens to become endemic in the region [6,7]. In Italy, a country where CRE are reported at endemic level [8], NDM-CRE were first detected in 2009 [9,10] and sporadic, often travel-related, cases have been recorded since [5].…”
Section: Public Health Implications and Conclusionmentioning
confidence: 99%
“…Plasmid prediction using whole genome sequences identified several putative types of plasmids harbored by the eight strains (Figure 4). Among these putative types of plasmids, IncHI2A, IncFIB(K), IncFII, IncFI1, IncR, IncHI2, and IncFIA plasmids carrying bla NDM-1 have been reported [33,34,35,36,37], while IncX4, IncFIB(K), IncFII, IncFI1, IncY, IncHI2, IncX1, and IncFIA plasmids carrying mcr-1 have been reported [38,39,40,41,42]. Although more accurate and reliable technologies such as the third-generation sequencing technologies are necessary for determining the accurate type and sequence of the plasmids, bioinformatical analysis using whole genome sequences revealed that an IncFII-type plasmid homologous to pHNEC55 (GenBank accession: KT879914) likely carried the bla NDM-1 gene, and an IncX4-type plasmid homologous to pIBMC_mcr1 (GenBank accession: MF449287) likely carried the mcr-1 gene, as the backbones of both plasmids were found in the genomes of the eight strains (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, ST 11 clones harbouring carbapenemase genes have been reported from countries around the world, especially PR China [3]. A K. pneumoniae ST11 strain harbouring bla NDM-1 had become predominant among CPE isolated in Poland [6]. Herein, we report the first identification of bla NDM-5 -harbouring K. pneumoniae ST11 isolates in clinical specimens from patients at Yangon General Hospital in Yangon, Myanmar.…”
mentioning
confidence: 89%